Fostering Environmental Character through Community-Based Groundwater Recharge Education in Coastal Lovina, Bali - Lufira, Rahmah Dara; Marsudi, Suwanto; Yuliani, Emma; Suhartanto, Ery; Hendrawan, Andre Primantyo; Utami, Rizki Tri (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2026)
Seawater intrusion and declining groundwater quality in coastal Lovina require more than purely technical responses that contribute to cultivating environmental values and the character of local communities. This paper describes a community-based education design for groundwater conservation through an infiltration-well siting plan and a pilot biopore installation in Kalibukbuk Village, Buleleng, Bali. We employed a participatory community service approach that integrated stakeholder coordination and interactive discussions with village authorities, community leaders, residents, and managers in charge of public facilities. Field observations were also performed to validate local constraints and opportunities for infiltration. Inputs from these discussions were synthesized into a context-based siting plan, which then guided the installation of four pilot biopores in a public area. The program was evaluated qualitatively using participatory observation and structured feedback collected during coordination meetings, site visits, and implementation activities. Results include an initial technical planning package identifying potential locations for infiltration wells and biopores, successful installation of four pilot biopores, and early indications of strengthened daily practices aligned with environmental character, such as organic-waste segregation for composting and improved groundwater-conservation literacy. These findings suggest that value education linked to tangible conservation actions can enhance community readiness for more sustainable groundwater management in coastal settings.